ALK‐positive (2p23 rearranged) anaplastic large cell lymphoma with localization to the skin in a pediatric patient. (5th February 2015) - Pulitzer, Melissa; Ogunrinade, Olakunle; Lin, Oscar; Steinherz, Peter
Abstract : Anaplastic large cell lymphoma (ALCL) either as primary cutaneous or nodal disease is rare in children and difficult to distinguish, which is important both prognostically and for treatment purposes. We present a case of anaplastic lymphoma kinase (ALK)+ skin‐limited ALCL that highlights this challenge and draws attention to pitfalls in assessing ALK status. The patient was an 11‐year old girl with a twice recurrent nodule on her right shoulder. Each biopsy revealed a deep infiltrate of atypical lymphocytes that expressed CD3, CD4, CD43, CD45RO and CD30. The initial biopsy was epithelial membrane antigen (EMA)+ with vague cytoplasmic ALK‐1 positivity by immunohistochemistry, while the second biopsy was EMA+ and nuclear ALK‐1+. Fluorescence in situ hybridization analysis for an ALK (2p23) rearrangement of the first specimen was negative, while an ALK gene rearrangement was present in the second specimen. Therefore, this case was treated as nodal ALCL, despite negative bone marrow and radiographic imaging studies. The patient was treated with combination chemotherapy and remains disease‐free. Demonstration of nuclear ALK‐positivity, ALK (2p23) gene rearrangement is suggestive of systemic ALCL. Without evidence of systemic disease, this case highlights challenges of skin‐limited ALCL, whose clinical behavior as either cutaneous ALCL systemic ALCL may not be immediately apparent.